Respuesta :

Answer:

okkkkkkkķkkkkkkkkkkkkk

Answer:

Step 1: Remove parentheses by multiplying factors.

= (x * x) + (1 * x) + (2 * x) + (2 * 1)

Step 2: Combine like terms by adding coefficients.

(x * x) = x2

(1 * x) = 1x

(2* x) = 2x

Step 3: Combine the constants.

(2 * 1) = 2

Step 4: Therefore, Simplifying Algebraic Expression is solved as

= x2 + 3x + 2.

Step-by-step explanation:

A cube is 3- dimensional shape with 6 equal sides, 6 faces, and 6 vertices in geometry. ... In 3 – dimension, the cube's sides are; the length, width, and height.